Entering the World of the Small Church - Pappas, Anthony G. (Rowman & Littlefield Publishers, 2000)
This demonstrates amazingly, with unflinching honesty and a wonderfully redeeming sense of humor, a resource especially helpful in motivating change and growth by mobilizing the natural strengths of small churches. For you who have been looking for a reliable guide to interpret the world of the small church, look no further since this provides all the insights you need. Includes images and models and strategies that reflect the profound uniqueness of the small church. It clearly shows leaders how to lead within the dynamics and culture of the small congregation. This is theologically sound and eminently practical. A must reading for anyone who is or plans to be a leader in a small church. Excellent for small roup study.